Short term durability of steel-strap confined concrete - Lee, Hoong Pin; Abdullah Zawawi, Awang; Wahid, Omar (Penerbit UTM Press, Universiti Teknologi Malaysia., 2016)
Steel strapping tensioning technique (SSTT) confinement has been proven as a type of external confinement to retrofit and upgrade concrete structures. Their remarkable enhancement to concrete mechanical properties, practicing active lateral confinement, low cost, easy to operate, time saving and no structure interruption during application have brought this technique as of the most affordable technique for column confinement, especially for high strength concrete (HSC) which naturally behaves insufficient in ductility. Although a great number of previous studies have demonstrated the performance of SSTT confinement, there are several anxieties related to the long term behaviour of SSTT confined columns which have yet been implemented especially in real hostile condition. Environmental effects, such as ultraviolet radiation exposure and saline solution (sea water) may affect the confining material properties, and therefore decrease the performance of the confined columns. In this study a total of twenty HSC specimens with dimension of 100 mm and 200 mm in diameter and height respectively were prepared, volumetric-identically pre-tensioned with steel strap and exposed to three conditions: indoor, outdoor and saline water for three months. The exposed specimens were monotonically tested and their performance was studied through the stress-strain relationship, mode of failure and degree of corrosion. The results show that none of the forenamed environmental conditions have exaggerating influence on the performance of the SSTT confined concrete specimens even some material has been severely corroded. It is then parallel compared with existing FRP confinement studies and the result proves that SSTT confinement able to possess the highest strength performance under similar environmental exposure.